Addressing the Challenges in Pediatric Facial Fractures: A Narrative Review of Innovations in Diagnosis and Treatment - Gabriel Mulinari-Santos; Amanda Paino Santana; Paulo Roberto Botacin; Roberta Okamoto (Surgeries)
Background/Objectives: Pediatric facial fractures present unique challenges due to the anatomical, physiological, and developmental differences in children’s facial structures. The growing facial bones in children complicate diagnosis and treatment. This review explores the advancements and complexities in managing pediatric facial fractures, focusing on innovations in diagnosis, treatment strategies, and multidisciplinary care. Methods: A narrative review was conducted, synthesizing data from English-language articles published between 2001 and 2024. Relevant studies were identified through databases such as PubMed, Scopus, Lilacs, Embase, and SciELO using keywords related to pediatric facial fractures. This narrative review focuses on anatomical challenges, advancements in diagnostic techniques, treatment approaches, and the role of interdisciplinary teams in management. Results: Key findings highlight advancements in imaging technologies, including three-dimensional computed tomography (3D CT) and magnetic resonance imaging (MRI), which have improved fracture diagnosis and preoperative planning. Minimally invasive techniques and bioresorbable implants have revolutionized treatment, reducing trauma and enhancing recovery. The integration of multidisciplinary teams, including pediatricians, psychologists, and speech therapists, has become crucial in addressing both the physical and emotional needs of patients. Emerging technologies such as 3D printing and computer-assisted navigation are shaping future treatment approaches. Conclusions: The management of pediatric facial fractures has significantly advanced due to innovations in imaging, surgical techniques, and the growing importance of interdisciplinary care. Despite these improvements, long-term follow-up remains critical to monitor potential complications. Ongoing research and collaboration are essential to refine treatment strategies and improve long-term outcomes for pediatric patients with facial trauma.